Relationship concept ‘autoimage’ and ‘heteroimage’ (Perception of the sociocultural aspects of novels): Взаимоотношение понятий «автоимидж» и «гетероимидж» (на материале художественных текстов) - Pešková, Michaela (Przegląd Wschodnioeuropejski, 2021)
The paper aims to introduce research in the field of the literary imagology and text semiotics. It focuses on the analysis of the creation of “autoimage”, or rather a self-image, and “hereroimage”, or a counter-mage, the image of otherness, as a means of shaping national identity, by interpreting the artistic texts written by the Czech writer Jáchym Topol and the Russian writer Vladimir Sorokin. It pays attention particularly to their novels from the first decade of the 21st century. The texts will be compared in a broader context of social discourse. Moreover, it will address the issue of the disproportion between the intensity of attention of one nation to another (Czech-Russian and Russian-Czech) and the differences in the perception of cultural distance.